(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this article, we first tried to prove Schwartz’s inequality and then discuss its application in the field of telecommunication systems, especially in the filtering of discrete and continuous white noise signals. Schwartz’s inequality is an extremely useful inequality that is used in various engineering optimization problems. For example, it is used in order to obtain the adapted filter as well as the maximum ratio combining technique that occurs in digital telecommunication systems.